A preliminary report on the medical profile of disabled persons living in Zhabei District, Shanghai, Mainland China - Chen, G.; Tan, Boon; Sun, X.; Meng, Xingqiong; Jiwa, Moyez (Radcliffe Medical Press Ltd., 2011)
Background: The prevalence of chronic diseases and their risk factors in different general populations are well documented, but little is known about disabled populations in China. Aims: The purpose of this study is to report available data on the medical profile of disabled persons living in Zhabei District, Shanghai, Mainland China. It also aimed to explore the association between any medical conditions, types and severity of disabilities and socio-demographic factors. Methods: Nine hundred and sixty-one disabled persons underwent physical medical examination to identify predisposing conditions for chronic diseases (hypertension and elevated glucose, lipids and triglyceride levels) and to diagnose two common chronic diseases – heart disease and diabetes. Logistic regression was used to assess the influence of age, gender, disability type, disability severity, education level, employment status, socio-economic status or marital status on chronic diseases and predisposing factors.Results: The mean age of the participants was 53(12.5) years. The most prevalent types of disability were physical disability (44.9%), visual impairment (28.8%) and intellectual disability (12.5%).Hyperlipidemia was most prevalent (17.1%), followed by hypertension (15.3%), heart disease (7.2%) and diabetes (6.0%). These conditions were not associated with the type or the severity of disability in this sample. Males were more likely to have hypertension (OR=1.75; 95% CI: 1.05, 2.93) and elevated triglycerides (OR=1.84; 95% CI: 1.05, 3.20). The unemployed (OR=4.80, 95% CI: 1.45, 15.76) and older participants (OR=1.04, 95% CI: 1.02, 1.07) were more likely to have elevated blood glucose levels. Divorced individuals were more likely to be diagnosed with heart disease (OR= 3.72; 95% CI: 1.37, 10.09) and those with better socio-economic backgrounds (OR=3.09; 95% CI: 1.05, 9.15) and the older disabled (OR=1.08,95% CI: 1.04, 1.12) were more likely to have diabetes. Conclusion: This preliminary study found that abnormal clinical findings were not related to the type or the severity of disability. Most abnormal findings were, however, related to increasing age, consistent with previous findings in the general Chinese population.